Extraoral implants in irradiated pacients - Piras de Oliveira, Joaquim Augusto; Abrahao, Marcio; Dib, Luciano Lauria [UNESP] (Assoc Brasileira Otorrinolaringologia & Cirurgia Cervicofacial, 2013)
The aim of this study is to analyze the success of extraoral osseointegrated implants used to support and contain prosthesis designed to rehabilitate craniofacial deformities.Method: This study was based on the retrospective assessment of charts from 59 patients submitted to cancer surgery and who received 164 extraoral implants to contain facial prosthesis.Results: Among 164 implants, 42 were fixed in previously irradiated regions. Eight of the implants did not have osseointegration; and from these, 2 were fixed in irradiated bone. The result show 116 (95.1%) successfully osseointegrated implants in non-irradiated sites. The success rate among 42 implants fixed in previously irradiated bones was 40 (95.3%) osseointegrated implants.Conclusion: The use of extraoral craniofacial implants represents a safe and effective approach to treat facial deformities as a support for the rehabilitation prosthesis. Radiotherapy treatment does not prevent osseointegration.
Keywords: osseointegration; prostheses and implants; radiotherapy